Genetic absolute dating based on microsatellites and the origin of modern humans. - Goldstein, D B (1995)
We introduce a new genetic distance for microsatellite loci, incorporating features of the stepwise mutation model, and test its performance on microsatellite polymorphisms in humans, chimpanzees, and gorillas. We find that it performs well in determining the relations among the primates, but less well than other distance measures (not based on the stepwise mutation model) in determining the relations among closely related human populations. However, the deepest split in the human phylogeny seems to be accurately reconstructed by the new distance and separates African and non-African populations. The new distance is independent of population size and therefore allows direct estimation of divergence times if the mutation rate is known. Based on 30 microsatellite polymorphisms and a recently reported average mutation rate of 5.6 x 10(-4) at 15 dinucleotide microsatellites, we estimate that the deepest split in the human phylogeny occurred about 156,000 years ago. Unlike most previous estimates, ours requires no external calibration of the rate of molecular evolution. We can use such calibrations, however, to test our estimate.